Profiling the New Immigrant Worker: The Effects of Skin Color and Height - Hersch, Joni (Journal of Labor Economics, 2008)
Using data from the New Immigrant Survey 2003, this article shows that skin color and height affect wages among new lawful immigrants to the United States, controlling for education, English language proficiency, occupation in source country, family background, ethnicity, race, and country of birth. Immigrants with the lightest skin color earn on average 17% more than comparable immigrants with the darkest skin color. Taller immigrants have higher wages, but weight does not affect wages. Controls for extensive current labor market characteristics that may be influenced by discrimination do not eliminate the negative effect of darker skin color on wages.